Fundamentals de Ciencia de Polimeros: Un Texto Introductorio - Iruin, Juan J (CRC Press, 2019)
This is a new, basic introduction to polymer science. It is both comprehensive and readable. The authors are leading educators in this field with extensive backgrounds in industrial and academic polymer research. The text starts with a description of the types of microstructures found in polymer materials. This provides an understanding of some of the key features of the various mechanisms of homopolymerization and copolymerization which are discussed in following chapters. Also discussed in these chapters are the kinetics and statistics of polymerization, with a separate chapter on the characterization of chain structure by spectroscopic methods. The next part of the text deals with chain conformation, structure and morphology, leading to a discussion of crystallization, melting and glass transition. The discussion then moves from solid state to solution properties where solution thermodynamics is introduced. This provides the basis for discussion of the measurement of molecular weight by various solution methods. The final chapter deals with mechanical and rheological properties which are discussed from a phenomenological continuum approach and then in terms of a fundamental molecular perspective. Altogether, this new text provides a comprehensive, readable introduction to and overview of polymer science. It is well illustrated with schematics prepared for this text to help in the understanding of key concepts. It will provide a basic understanding of today's polymer science for technical and engineering personnel not already familiar with the subject, and a convenient update and overview for materials scientists.